Communication competence in pilot-controller interactions : repair and accommodation strategies - Haryani Hamzah,; Pramela Krish,; Afendi Hamat, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Due to the exponential growth in the aviation industry, the number of non-native speaker pilots and air traffic controllers has significantly increased. Naturally, the interaction has become more challenging since the communication shifted to intercultural communication within a lingua franca setting. This study identifies and discusses the repair and accommodation strategies pilots and air traffic controllers use in their routine in-flight communication. The corpus consists of 30 hours of actual pilot-controller audio communication collected from the Malaysian airspace. Audio data collected from three frequencies (Alpha, Bravo and Charlie) were analysed using the conversation analysis method. The findings extend existing knowledge on miscommunications in pilot-controller discourse. The study found that in most instances, pilots and controllers made conscious efforts to repair the various types of miscommunications that took place. The findings also show that communication errors and misunderstandings are commonly caused by cultural differences and inadequate language competency amongst the pilots and controllers. The paper concludes by suggesting that repair strategies and intercultural communication competence should be integrated within aviation communication training modules to improve pilot and controller communication strategies in intercultural settings.